Development of Genistein Synthesis for Use as a Certified Reference Material - A. A. Zhigalina; V. G. Dudarev; V. V. Tikhonova; O. Yu. Strelova (Разработка и регистрация лекарственных средств, 2021)
Introduction. The use of certified reference materials (CRMs) ensures metrological traceability and comparability of analysis results performed in different laboratories, by different analysts, at different times. Genistein is a promising substance with a wide spectrum of pharmacological action. genistein is widely used in dietary supplements. Development of regulatory documents for CRM of genistein will ensure the quality of drugs and dietary supplements.Aim. Aim of our study is to improve of the ways of synthesis and determination of spectrum characteristics of genistein for the certification of CRM.Materials and methods. We used synthetic genistein, (Ph.D. V. Yu. Kovtun SPC "Pharmzashchita") (sample № 1) and genistein synthesized and studied at the departments of pharmaceutical chemistry and chemical technology of medicinal substances SPCPU (sample № 2). Infrared spectra of genistein samples were collected on an FSM 1201 infrared Fourier spectrometer (OOO Infraspek, Russia) via KBr pellets technique. All the spectra were collected in the 4000–500 cm−1 range. The NMR (1H and 13C) measurements were performed with a BrukerAvance III NMR spectrometer (400 and 100 MHz) (Bruker, Germany) in DMSO-d6 solvent. Raman spectra were recorded by an ORTES-785TRS-2700 analytical Raman scattering system at a laser power of 100 mW (OPTEC JSC, Russia). Laser interaction time was 5, 10, 20 and 60 seconds. The results were processed using the software "BWSpec 4.10_4", USA. GC-MS was performed on an Agilent Technologies 7890A gas chromatograph (Agilent Technologies, USA) with a 7693 autoinjector and a Hewlett Packard 5975C mass selective detector.Results and discussion. The synthesis was carried out according to the developer's method. The stage "removal of the alkyl protection" has been improved. The spectra of the synthesis intermediate of genistein (biochanin A) correspond to the literature data. Samples of genistein were investigated by methods: MC and NMR 13С, 1Н. The structure of the investigated substance was confirmed; Raman and IR spectroscopy showed that the spectra of the samples do not differ from each other and there are no additional signals.Conclusion. The spectrum characteristics of samples of genistein were obtained by NMR, IR and Raman spectroscopy, which will be used in the regulatory documentation for CRM of genistein. All of this will make it possible to control the quality of medicines based on it and to identify substandard dietary supplements.